Voltage rise due to inter-connection of embedded generators to distribution network on weak feeder - Mekhilef, Saad; Chard, T.R.; Ramachandramurthy, V.K. (2009)
This paper presents voltage rise due to inter-connection of embedded generators to distribution network on weak feeder. Studies were performed on Malaysia's 11kV network using a simulation tool called PSS ADEPTâ¢. Various scenarios were investigated such as EG penetration level, location of EG plant, sizing of feeder (distance from MAIN substation), loading of network, Automatic Voltage Control relay set point at MAIN substation, power factor of network and various operating mode of EG. It is concluded that the introduction of EG at the distribution network will cause voltage rise and this leads to customer voltages being out of the allowable range. Through careful design of the connection arrangement, Distribution Network Operator (DNO) can ensure that the new EG connection does not cause problems and at the same time, enhance the performance of the network.